Effects of Labelling and Increasing the Proportion of Lower-Energy Density Products on Online Food Shopping: A Randomised Control Trial in High- and Low-Socioeconomic Position Participants - Marty, Lucile; Cook, Brian; Piernas, Carmen; Jebb, Susan A.; Robinson, Eric (Nutrients, 2020)
Reducing the energy density (ED) of product selections made during online supermarket food shopping has potential to decrease energy intake. Yet it is unclear which types of intervention are likely to be most effective and equitable. We recruited 899 UK adults of lower and higher socioeconomic position (SEP) who completed a shopping task in an online experimental supermarket. Participants were randomised in a 2 × 2 between-subjects design to test the effects of two interventions on the ED of shopping basket selections: labelling lower-ED products as healthier choices and increasing the relative availability of lower-ED products within a range (referred to as proportion). Labelling of lower-ED products resulted in a small but significant decrease (−4.2 kcal/100 g, 95% CIs −7.8 to −0.6) in the ED of the shopping basket. Increasing the proportion of lower-ED products significantly decreased the ED of the shopping basket (−17 kcal/100 g, 95% CIs −21 to −14). There was no evidence that the effect of either intervention was moderated by SEP. Thus, both types of intervention decreased the ED of foods selected in an online experimental supermarket. There was no evidence that the effectiveness of either intervention differed in people of lower vs. higher SEP.